Understanding forest transitions and lock-ins in Latin American agro-forest frontiers: aligning theory to practice for accelerating restoration - Madelon Lohbeck; Thomas W. Kuyper; Frans Bongers; Rocío Aguilar-Fernández; Patricia Balvanera; Jelle Behagel; Carolina Berget; Felix Bianchi; Irene Maria Cardoso; Lucas de Carvalho Gomes; Juana Cruz-Morales; Mathieu Decuyper; et al. (Global Environmental Change, 2026)

Application of quinoa oil emulsions in fresh goat cheese: effects on lipid profile, technological properties and microstructure - Nuria Muñoz-Tebar; Raquel Lucas-González; Clara Muñoz-Bas; Gema Martínez-Navarrete; Manuel Viuda-Martos; Estrella Sayas-Barberá; Eduardo Fernández; José Ángel Pérez-Alvarez; Juana Fernández-López (Food Chemistry, 2026)

Deciphering Crossed Cerebellar Diaschisis in Patients with Large-Vessel Occlusion Acute Ischemic Stroke using BOLD Cerebrovascular Reactivity - Jacopo Bellomo; Vittorio Stumpo; Christiaan Hendrik Bas van Niftrik; Susanne Wegener; Andreas Luft; Zsolt Kulcsar; Luca Regli; Jorn Fierstra; Martina Sebök (The Cerebellum, 2026)

Exploring the suitability of Tenebrio molitor powder (whole and defatted by supercritical CO2) as a partial fat replacement in bologna-type sausages - J. Rodríguez-Párraga; R. Lucas-González; M. Viuda-Martos; C. Muñoz-Bas; F.J. Barba; J.A. Pérez-Alvarez; J. Fernández-López (Meat Science, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

A food-web assessment model for marine mammals, fish, and fisheries in the Norwegian and Barents Seas - Benjamin Planque; Lucas Bas; Martin Biuw; Marie-Anne Blanchet; Bjarte Bogstad; Elena Eriksen; Hilaire Drouineau; Cecilie Hansen; Bérengère Husson; Erik Askov Mousing; Christian Mullon; Torstein Pedersen; et al. (Progress in Oceanography, 2024)

Environmental Life Cycle Assessment of multi-use of marine space: A comparative analysis of offshore wind energy and mussel farming in the Belgian Continental Shelf with terrestrial alternatives - Laura Vittoria De Luca Peña; Bilge Bas; Jo Dewulf; Sander W.K. van den Burg; Sue Ellen Taelman (Journal of Cleaner Production, 2024)

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Topographic volume-standardization atlas of the human brain - Kevin Akeret; Christiaan Hendrik Bas van Niftrik; Martina Sebök; Giovanni Muscas; Thomas Visser; Victor E. Staartjes; Federica Marinoni; Carlo Serra; Luca Regli; Niklaus Krayenbühl; Marco Piccirelli; Jorn Fierstra (Brain Structure and Function, 2021)
Specific anatomical patterns are seen in various diseases affecting the brain. Clinical studies on the topography of pathologies are often limited by the absence of a normalization of the prevalence of pathologies to the relative volume of the affected anatomical structures. A comprehensive reference on the relative volumes of clinically relevant anatomical structures serving for such a normalization, is currently lacking. The analyses are based on anatomical high-resolution three-dimensional T1-weighted magnetic resonance imaging data of 30 healthy Caucasian volunteers, including 14 females (mean age 37.79 years, SD 13.04) and 16 males (mean age 38.31 years, SD 16.91). Semi-automated anatomical segmentation was used, guided by a neuroanatomical parcellation algorithm differentiating 96 structures. Relative volumes were derived by normalizing parenchymal structures to the total individual encephalic volume and ventricular segments to the total individual ventricular volume. The present investigation provides the absolute and relative volumes of 96 anatomical parcellation units of the human encephalon. A larger absolute volume in males than in females is found for almost all parcellation units. While parenchymal structures display a trend towards decreasing volumes with increasing age, a significant inverse effect is seen with the ventricular system. The variances in volumes as well as the effects of gender and age are given for each structure before and after normalization. The provided atlas constitutes an anatomically detailed and comprehensive analysis of the absolute and relative volumes of the human encephalic structures using a clinically oriented parcellation algorithm. It is intended to serve as a reference for volume-standardization in clinical studies on the topographic prevalence of pathologies.

Crossed Cerebellar Diaschisis Indicates Hemodynamic Compromise in Ischemic Stroke Patients - Lita von Bieberstein; Christiaan Hendrik Bas van Niftrik; Martina Sebök; Mohamad El Amki; Marco Piccirelli; Christoph Stippich; Luca Regli; Andreas R. Luft; Jorn Fierstra; Susanne Wegener (Translational Stroke Research, 2021)
Crossed cerebellar diaschisis (CCD) in internal carotid artery (ICA) stroke refers to attenuated blood flow and energy metabolism in the contralateral cerebellar hemisphere. CCD is associated with an interruption of cerebro-cerebellar tracts, but the precise mechanism is unknown. We hypothesized that in patients with ICA occlusions, CCD might indicate severe hemodynamic impairment in addition to tissue damage. Duplex sonography and clinical data from stroke patients with unilateral ICAO who underwent blood oxygen-level-dependent MRI cerebrovascular reserve (BOLD-CVR) assessment were analysed. The presence of CCD (either CCD+ or CCD−) was inferred from BOLD-CVR. We considered regions with negative BOLD-CVR signal as areas suffering from hemodynamic steal. Twenty-five patients were included (11 CCD+ and 14 CCD−). Stroke deficits on admission and at 3 months were more severe in the CCD+ group. While infarct volumes were similar, CCD+ patients had markedly larger BOLD steal volumes than CCD− patients (median [IQR] 122.2 [111] vs. 11.6 [50.6] ml; p < 0.001). Furthermore, duplex revealed higher peak-systolic flow velocities in the intracranial collateral pathways. Strikingly, posterior cerebral artery (PCA)-P2 velocities strongly correlated with the National Institute of Health Stroke Scale on admission and BOLD-CVR steal volume. In patients with strokes due to ICAO, the presence of CCD indicated hemodynamic impairment with larger BOLD-defined steal volume and higher flow in the ACA/PCA collateral system. Our data support the concept of a vascular component of CCD as an indicator of hemodynamic failure in patients with ICAO.

Crossed Cerebellar Diaschisis in Patients with Diffuse Glioma Is Associated with Impaired Supratentorial Cerebrovascular Reactivity and Worse Clinical Outcome - Martina Sebök; Christiaan Hendrik Bas van Niftrik; Matthias Halter; Aimee Hiller; Katharina Seystahl; Athina Pangalu; Michael Weller; Christoph Stippich; Luca Regli; Jorn Fierstra (The Cerebellum, 2020)
Crossed cerebellar diaschisis (CCD) can be associated with impaired cerebrovascular reactivity (CVR) and poor clinical outcome, but whether this holds true for patients with diffuse glioma is unknown. With blood oxygenation level–dependent (BOLD)-CVR imaging, we determined the presence of CCD in patients with diffuse glioma and investigated its relationship with cerebrovascular reactivity and clinical outcome. For eighteen enrolled subjects (nineteen datasets) with diffuse glioma, CCD was deferred from BOLD-CVR using a predetermined cerebellar asymmetry index (CAI) cutoff value of 6.0%. A FET-PET study was done as a verification of the CCD diagnosis. BOLD-CVR values as well as clinical performance scores (i.e., Karnofsky performance score (KPS), disability rating scale (DRS), and modified Rankin scale (mRS)) by BOLD-CVR scan at 3-month clinical follow-up were assessed and compared for the CCD-positive and CCD-negative group. CCD was present in 26.3% of subjects and strongly associated with impaired BOLD-CVR of the affected (i.e., the hemisphere harboring the glioma) and unaffected supratentorial hemisphere (CCD(+) vs. CCD(−): 0.08 ± 0.11 vs. 0.18 ± 0.04; p = 0.007 and 0.08 ± 0.12 vs. 0.19 ± 0.04; p = 0.007, respectively). This finding was independent of tumor volume ( p = 0.48). Furthermore, poorer initial (by scan) clinical performance scores at follow-up were found for the CCD(+) group. The presence of crossed cerebellar diaschisis in patients with diffuse glioma is associated with impaired supratentorial cerebrovascular reactivity and worse clinical outcome.

Quantifiable risk–benefit assessment of micronutrients: From theory to practice - Lisette Krul; Bas H. A. Kremer; Niels B. Lucas Luijckx; Winfried R. Leeman (Critical Reviews in Food Science and Nutrition, 2017)

Multi-model comparison of the economic and energy implications for China and India in an international climate regime - Daniel J. A. Johansson; Paul L. Lucas; Matthias Weitzel; Erik O. Ahlgren; A. B Bazaz; Wenying Chen; Michel G. J. den Elzen; Joydeep Ghosh; Maria Grahn; Qiao-Mei Liang; Sonja Peterson; Basanta K. Pradhan; et al. (Mitigation and Adaptation Strategies for Global Change, 2015)

Soil spectroscopy: an opportunity to be seized - Marco Nocita; Antoine Stevens; Bas van Wesemael; David J. Brown; Keith D. Shepherd; Erick Towett; Ronald Vargas; Luca Montanarella (Global Change Biology, 2015)

Enhancing the relevance of Shared Socioeconomic Pathways for climate change impacts, adaptation and vulnerability research - Bas J. van Ruijven; Marc A. Levy; Arun Agrawal; Frank Biermann; Joern Birkmann; Timothy R. Carter; Kristie L. Ebi; Matthias Garschagen; Bryan Jones; Roger Jones; Eric Kemp-Benedict; Marcel Kok; et al. (Climatic Change, 2014)

Stabilizing greenhouse gas concentrations at low levels: an assessment of reduction strategies and costs - Detlef P. van Vuuren; Michel G. J. den Elzen; Paul L. Lucas; Bas Eickhout; Bart J. Strengers; Bas van Ruijven; Steven Wonink; Roy van Houdt (Climatic Change, 2007)

Differences in the effects of model inducers of cytochrome P450 on the biotransformation of scoparone in rat and hamster liver - Wim C. Mennes; Niels B. Lucas Luijckx; Heleen M. Wortelboer; Jan Noordhoek; Bas J. Blaauboer (Archives of Toxicology, 1993)